“Embarazo gemelar: Complicaciones obstétricas en el hospital apoyo iquitos “Cesar Garayar García” período Enero – Diciembre 1995” - Portocarrero García, Lydy (1996)
A study of 38 cases of twin pregnancy that occurred in Hospital support! quitos Ga Caesar scratch Giu-cia, during the period e:rnt re Jan ro ·· December 1995; for every case of pregnant twin randomly selected a case of single pregnancy, with the aim of identifying the complications in the mother and the newborn, to determine the relative risk of these and the mortality rate specific for this serine. The frequency of submission 01 case of twin pregnancy ~ Jr each 69 unique pregnancy) is similar to the otr·os authors. Was to determine the relative risk of occurring maternal complications being more E.; Igni fica you vos to the threat of abortion (RR: 9. 82 P